Assessment of pain in different types of labor in puerperal at Hospital de Clínicas de Passo Fundo (Research, Society and Development, 2022)
The puerperium ismark ed by the woman's intense physical and emotional involvement, and it is during this period that discomfort can arise and compromise the patient's quality of life. In addition, the occurrence of pain among mothers, whether acute or chronic, may be related to the type of delivery performed. In this sense, the main objective of this research was to analyze pain in different types of delivery in puerperal women at the Hospital de Clínicas de Passo Fundo according to the Visual Analogue Scale (VAS), in addition to analyzing the type of delivery performed: vaginal, vaginal instrumented or cesarean section, estimate the intensity of pain determined by the puerperal women in the immediate postpartum period and at the time they were interviewed (current pain), took the location of the pain and relate it to the performed mode of delivery, and compare the pain in nulliparous and multiparous. This is a descriptive, quantitative and cross-sectional analytical study in which the population corresponds to the puerperal women, who entered the Maternity Hospital of the Hospital de Clínicas de Passo Fundo (HCPF) and which had, regardless of the route to be performed, within of the first 48 hours of hospitalization, from September to November 2020. Data were transmitted using descriptive statistics, comparison tests and association of variables. Procedures The statisticians were performed using the statistical software Statistical Package for Social Sciences (SPSS ®, V. 25). The research sample consisted of 53 mothers, aged between 16 and 43 years. There was a predominance of puerperal women aged between 22 and 30 years old (45.3%) and also a predominance of cesarean sections (58.5%), according to the other studies researched on the subject. In addition, of the 20 normal deliveries, in 60% of the cases an episiotomy was required (n = 12). The places most affected by pain were in the lower abdomen (n = 26, 49.1%), followed by the abdominal region (34%). Finally, no summary difference was found between the immediate postpartum pain scale and the current pain scale (at the time of the interview) between nulliparous and multiparous women (p> 0.05).